Stanley Milgram e a interpretação sectária nos textos de Qumran - Silva, Sidney Matos da (2013)
The aim of this research is to verify which psychosocial factors present in a certain environment determine or favour the establishment of a new interpretation of a text or situation. The Stanley Milgram experiment to determine which factors impose certain behaviors was used as the starting point. This research proves the hypothesis that the factors which impose behaviors are also present in imposing a specific interpretation. For this purpose, in the first chapter, the experiment carried out by Milgram in Yale University in the year 1962 concerning the obedience to authority was analyzed, and from this experiment were drawn the variables which determine the behavior of the volunteers. In the second chapter, the sectarian scriptures of the Dead Sea community, specifically of Qumran were analyzed, verifying that changes of interpretation of the canonical text occurred, focusing on the book of Habakkuk. In the third chapter it is demonstrated that the same factors presented in the Milgram experiment were found in the Qumran community and were reflected in the sectarian texts. Other historical events are also shown which provide evidence of the same variables confirming the hypothesis. In sequence, some suggestions are made for further future scientific analysis.